2001
DOI: 10.1016/s0002-9440(10)61782-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lipid Rafts in Nephrin Phosphorylation and Organization of the Glomerular Slit Diaphragm

Abstract: NPHS1 has recently been identified as the gene whose mutations cause congenital nephrotic syndrome of the Finnish type. The respective gene product nephrin is a transmembrane protein expressed in glomerular podocytes and primarily localized to the glomerular slit diaphragm. This interpodocyte junction functions in the glomerular filtration by restricting the passage of plasma proteins into the urinary space in a size-selective manner. The functional role of nephrin in this filtration process is so far not very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 37 publications
7
131
0
1
Order By: Relevance
“…Hereby, they provide molecular frameworks for numerous cell biologic processes, such as exocytosis and endocytosis, cell adhesion, and signal transduction events (86 -88). Recent work from our lab established that lipid raft microdomains are critical for the dynamic functional organization of the SD (89). We have shown that nephrin associates with lipid rafts and coimmunoprecipitates with a podocyte-specific 9-O-acetylated ganglioside (89).…”
Section: Involvement Of Lipid Rafts In Functional Organization Of the Sdmentioning
confidence: 83%
See 2 more Smart Citations
“…Hereby, they provide molecular frameworks for numerous cell biologic processes, such as exocytosis and endocytosis, cell adhesion, and signal transduction events (86 -88). Recent work from our lab established that lipid raft microdomains are critical for the dynamic functional organization of the SD (89). We have shown that nephrin associates with lipid rafts and coimmunoprecipitates with a podocyte-specific 9-O-acetylated ganglioside (89).…”
Section: Involvement Of Lipid Rafts In Functional Organization Of the Sdmentioning
confidence: 83%
“…Recent work from our lab established that lipid raft microdomains are critical for the dynamic functional organization of the SD (89). We have shown that nephrin associates with lipid rafts and coimmunoprecipitates with a podocyte-specific 9-O-acetylated ganglioside (89). The in vivo injection of an antibody against this ganglioside causes morphologic changes of the filtration slits resembling FP effacement.…”
Section: Involvement Of Lipid Rafts In Functional Organization Of the Sdmentioning
confidence: 86%
See 1 more Smart Citation
“…In rat kidneys, preliminary results indicate that ABL1 localizes with nephrin in caveolae subdomains, known to functionally organize signaling pathways (Simons et al, 2001), is present in rat glomerular podocytes, and its expression level is downregulated in MNS and NB glomerular podocytes, as well as nephrin, compared with MHS and NA.…”
Section: Rostafuroxin Protects From Podocyte Damagementioning
confidence: 91%
“…This interaction was only detectable after solubilization of kidney lysates with 20 mM CHAPS, indicating that a substantial fraction of both proteins is associated with lipid rafts. Addition of 3 mM ATP to the lysis buffer appeared to increase the amount of NEPH1, precipitated with anti-nephrin antiserum versus protein G alone ( Figure 4D, lower panel), indicating that association with both lipid rafts (14) and the cytoskeleton (15) reduces the solubility of NEPH1 and/or nephrin and limits the experimental approaches to verify this interaction in vivo.…”
Section: Neph1 Forms Heterodimers With Nephrinmentioning
confidence: 99%